Makna Tubuh bagi Mahasiswi Bercadar di Yogyakarta: Kajian Sosiologi Tubuh - Fitriyah, Anis (FIKRAH, 2018)
Students who wear a veil got the radical stamp.  This article aims to see the body's meaning constructed by veiled students from the perspective of the sociology body. The method used is descriptive with a qualitative approach. The result shows that the body is divided into four regions. First, the meaning of the body from the constructionist perspective relating to the dimensions of weight and gender. Second, the body is understood as a cultural representation of social order and power. It relates to the social meaning of humans. The social meaning is constructed on positive and negative life activities. Third, the body is an agent and the veil is identity. Fourth, humans learn physical practices that are needed in everyday life to show social class position.